2011
DOI: 10.1111/j.1600-0412.2011.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical precancerous lesions – chromosomal instability in peripheral blood lymphocytes in relation to lesion stage, age and smoking habits

Abstract: The results suggest that MN frequency in PBL of patients with cervical precancerous lesions corresponds to an increase of chromosomal damage, irrespective of smoking habits, miscarriages, abortions and lesion stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Moreover, with more than half a million new cases and 275,000 deaths per year, cervical cancer continues to constitute a major public health problem and particularly affects young women in developing countries [2, 3]. Cervical cancer develops through a multistep process, with three cervical intraepithelial neoplasia grades, 1 to 3 (CIN1-3) [4]. However, it will take several years, even decades, from pre-cancer to invasive cervical cancer, which offers us many opportunities for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with more than half a million new cases and 275,000 deaths per year, cervical cancer continues to constitute a major public health problem and particularly affects young women in developing countries [2, 3]. Cervical cancer develops through a multistep process, with three cervical intraepithelial neoplasia grades, 1 to 3 (CIN1-3) [4]. However, it will take several years, even decades, from pre-cancer to invasive cervical cancer, which offers us many opportunities for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Werkmeister et al [26] reported that some genotoxic secretions are released by tumor tissues into the bloodstream, which might cause the significant increase in DNA damage [27], sister chromatid exchanges [13,28,29], micronuclei [12,3032], and chromosome aberrations (chromatid-type, chromosome-type, and asymmetric aberrations) [32] observed in leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer develops through a multistep process, with three cervical intraepithelial neoplasia grades, 1 to 3 (CIN1-3; ref. 4). The transition from CIN to invasive cancer will take several years, even decades, which offers us many opportunities for intervention and only a minority of the infected individuals go on to develop invasive cervical cancer (5).…”
Section: Introductionmentioning
confidence: 99%